Individual- and group-level consequences of divergence in perceived group affect - Jeong, Sophia Soyoung; Korsgaard, M Audrey (Human relations (New York), 2022)
The shared mood or affect of a work group can exert a powerful influence on the group’s social dynamics and effectiveness. However, the mood of others can be difficult to read, leading to divergent perceptions of group affect among members. What happens when individuals perceive the group’s affect differently? We answer this question by investigating how divergence in perceptions of group affect influences individuals’ social integration and the group’s performance. In doing so, we examine the implications of divergence in perceived group affect for individuals and the group as a whole. In a field study of 1419 individuals in 107 work groups, we found that divergence in perceptions of the group’s positive affect was negatively associated with individuals’ commitment to the team and undermined the positive impact of group affect on group performance. We discuss the implications of our findings for refining theory on group affect, the value of strongly shared affect, and how leaders can foster a stronger sense of shared affect within groups.